An electronic university library user’s status: developing a concept and evaluation criteria - R. A. Baryshev (Библиосфера)
The article considers an approach of educational activity assessment of a university electronic library, which advantage is in collecting information about users, analyzing their personal data, requests, search history and offering library services for advanced requests. In this case the context is information about users available to a library. This information obtains dynamics determined by the changing user’s status (moving from academic year to year, entering master’s program, postgraduate courses, etc.), his interests and information needs related to academic and scientific activities, hobbies, which are able changing over time.